2007
DOI: 10.1007/s11239-007-0079-8
|View full text |Cite
|
Sign up to set email alerts
|

Changes in haemocoagulation in healthy volunteers after a 1-hour thrombotripsy using a diagnostic 2–4 MHz transcranial probe

Abstract: Thrombotripsy with 1-hour TCD monitoring using a 2-4 MHz diagnostic probe may affect the fibrinolytic system in humans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 12 publications
0
21
0
Order By: Relevance
“…29 Results of the present study also support the safety and efficacy of sonolysis for prevention of periprocedural brain ischemic lesions in patients undergoing Unlike studies using sonolysis in acute stroke patients, not a direct effect of ultrasound waves on the clot but mainly an activation of fibrinolytic system was used in the SONOBUS-TER Trial and in the presented SONORESCUE Trial. 29,30 Published studies have demonstrated the effect of sonolysis on acceleration of arterial recanalization when combined with intravenous thrombolysis in patients with acute stroke. 9,15,16 Moreover, recent studies have also shown the effect of sonolysis on activation of endogenous fibrinolytic enzymes in healthy volunteers 30 and acute-stroke patients without application of thrombolytic agents.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…29 Results of the present study also support the safety and efficacy of sonolysis for prevention of periprocedural brain ischemic lesions in patients undergoing Unlike studies using sonolysis in acute stroke patients, not a direct effect of ultrasound waves on the clot but mainly an activation of fibrinolytic system was used in the SONOBUS-TER Trial and in the presented SONORESCUE Trial. 29,30 Published studies have demonstrated the effect of sonolysis on acceleration of arterial recanalization when combined with intravenous thrombolysis in patients with acute stroke. 9,15,16 Moreover, recent studies have also shown the effect of sonolysis on activation of endogenous fibrinolytic enzymes in healthy volunteers 30 and acute-stroke patients without application of thrombolytic agents.…”
Section: Discussionmentioning
confidence: 99%
“…29,30 Published studies have demonstrated the effect of sonolysis on acceleration of arterial recanalization when combined with intravenous thrombolysis in patients with acute stroke. 9,15,16 Moreover, recent studies have also shown the effect of sonolysis on activation of endogenous fibrinolytic enzymes in healthy volunteers 30 and acute-stroke patients without application of thrombolytic agents. 9,17,18 The mechanisms responsible for a reduced prevalence and volume of lesions after sonolysis in the present study could include acceleration of enzymatic fibrinolysis by the direct activation of a fibrinolytic system and increased transport of fibrinolytic agents (eg, plasmin) into the thrombus by mechanical disruption of thrombus structure, destruction of gaseous bubbles, and transient peripheral vasodilatation.…”
Section: Discussionmentioning
confidence: 99%
“…1,2,4,6,14,[20][21][22][23] ), the effect of TCD monitoring in acute IS patients was reported for the first time in 2000 (ref. 24 ) and the results of the first randomized study, testing the effect of sonothrombolysis showed the safety and efficacy of sonothrombolysis using the diagnostic 2-MHz TCD probe 7 .…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, mechanical effect caused by the thrombus vibration may lead to the acceleration of the penetration of fibrinolytics 3 . Secondly, non-thermal mechanisms -increasing the transport of fibrinolytic agents into the thrombus by mechanical disruption of its structure 24 , direct activation of fibrinolytic enzymes 14,15 , transient peripheral vasodilatation caused probably by increased production of nitrite oxide in the endothelium 21,26 also play a role in clot dissolution. However, confirmation of different effects on thrombus dissolution using various ultrasound frequencies and intensities are still missing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation